Editorial comment: Moderate aneuryms of the ascending aorta in stenotic bicuspid aortic valve - life threatening or merely an epiphenomenon? - Kallenbach, Klaus (European journal of cardio-thoracic surgery, 2012)
The current US guidelines for the diagnosis and management of patients with thoracic aortic disease recommend an operation for asymptomatic patients with bicusp